Surgical hand preparation metode handscrub dan handrub berbasis antiseptik: A scoping review - Olivia, Claudia; Ibrahim, Kusman; Kurniawan, Titis (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Healthcare-associated infections (HAIs) are complications of healthcare that can increase morbidity, mortality, length of hospitalization, and additional costs, including surgical site infections (SSIs) caused by various factors such as microorganisms from the surgical environment. One important step in preventing SSIs is surgical hand preparation using antimicrobial soap or alcohol-based fluids which aims to reduce microorganisms, prevent infection, and increase the success of surgical procedures according to WHO and CDC guidelines. Purpose: To determine the effectiveness of implementing surgical hand preparation using antiseptic-based hand washing and hand rubbing methods. Method: Scoping review with article sources from PubMed, Scopus, and ScienceDirect published in the last 6 years in the period 2018-2024. The keywords used are